Effect of additive concentration on crystalline surface of ZnO nanostructures morphology for enhanced humidity sensing - Riza, Muhammad Arif; Go, Yun Ii; Harun, Sulaiman Wadi; Ahmad Anas, Siti Barirah (KeAi Publishing Communications, 2022)
Zinc oxide (ZnO) possesses unique nanostructures. Most ZnO nanostructures have yet seen its use as coating for fiber Bragg grating (FBG) sensors. The properties of zinc oxide nanostructure can be greatly influenced by different additives added with the precursor. This study reports on the influence of different concentration of hexamethylenetetramine (HMT) additive towards the humidity sensing capability of zinc oxide coated on FBG sensors. The synthesis of zinc oxide nanostructure was through a modified hydrothermal method. Morphology observation has confirmed a unique hybrid of nanoflake, and porous hemispherical growth of zinc oxide accompanied with elemental analysis for validation. Sensor response towards change in relative humidity is improved by 400% with functional range between 40 and 80 RH%. The concentration of HMT to achieve such performance is 0.05 ​M with a zinc acetate precursor. The device shows potency with its hybrid nanostructure when integrated with FBG based humidity sensor. Due to its functional range, it can detect relative humidity contents in the air for various industries. The fabricated sensing device is suited for use in industries with several magnetic equipment and requiring many sensor nodes for mapping of data.